Estimation of Primary Productivity of Phytoplankton in the Inner Gulf of Thailand - Jaroensuk, Preyanut; Bunyajetpong, Sutaporn; Sojisuporn, Pramot; Lirdwitayaprasit, Thaithaworn (Burapha Science Journal, 2026)
The study of primary productivity of surface seawater in the inner Gulf of Thailand using O2 light-dark bottle method was conducted during June 2017, October 2017 and April 2018. The primary productivity was in the range of 0.47 to 116.88 mg C m-3 h-1. Its average was highest in the river-mouth region and declined toward the east coast, the west coast, the central region and the open region (41.12±29.90 20.59±6.40 8.82±5.23 3.43±1.46 and 0.47±0.00 mg C m-3 h-1). For seasonal primary productivity, its average was highest in the changing-monsoon season and declined toward the southwest monsoon and the summer (19.89±17.29 16.94±9.67 and 13.73±3.94 mg C m-3 h-1). Furthermore, the investigation of size-fractionated primary productivity with 13C method was carried out during April 2018. The result revealed that its average of (a) microphytoplankton, (b) nanophytoplankton and (c) picophytoplankton in the river-mouth region, the west coast and the open region were (a) 4.17 0.61 0.17, (b) 1.68 0.25 0.06 and (c) 1.40 0.66 0.28 mg C m-3 h-1, respectively. The proportion of primary productivity of microphytoplankton and nanophytoplankton was high in the river-mouth region and declined toward the west coast and the open region whereas the reverse was true for picophytoplankton. Although, picophytoplankton contributed the low proportion of primary productivity at the river-mouth region, but its primary productivity per chlorophyll a unit (PP/Chl a) was higher than that of microphytoplankton and nanophytoplankton (7.35-92.11, 0.76-33.67 and 0.80-8.65 mg C mg Chl a-1 h-1) in every station and region.